2009
DOI: 10.1002/adma.200803536
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Gas Sensing Based on Electron Transfer between Discrete Tin Oxide Nanocrystals and Multiwalled Carbon Nanotubes

Abstract: A new gas‐sensing platform for low‐concentration gases (NO2, H2, and CO) comprises discrete SnO2 nanocrystals uniformly distributed on the surface of multiwalled carbon nanotubes (CNTs). The resulting hybrid nanostructures are highly sensitive, even at room temperature, because their gas sensing abilities rely on electron transfer between the nanocrystals and the CNTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
221
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 285 publications
(236 citation statements)
references
References 41 publications
7
221
1
Order By: Relevance
“…Since the thermal treatment removes NO 2 lodged within vacancies, structural defects and oxygen functional groups, it can increase the recovery time. On the other hand, this thermal treatment creates an obstacle by preventing to bind higher-enersensitivity than other graphene-based NO 2 gas sensors [6,9,10,20]. Furthermore, the maximum response of our MLG device to 5 ppm is 38.7%, about 2.7 times higher than the CNTs/reduced graphene hybrid gas sensor previously reported by our group [13].…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…Since the thermal treatment removes NO 2 lodged within vacancies, structural defects and oxygen functional groups, it can increase the recovery time. On the other hand, this thermal treatment creates an obstacle by preventing to bind higher-enersensitivity than other graphene-based NO 2 gas sensors [6,9,10,20]. Furthermore, the maximum response of our MLG device to 5 ppm is 38.7%, about 2.7 times higher than the CNTs/reduced graphene hybrid gas sensor previously reported by our group [13].…”
Section: Methodsmentioning
confidence: 66%
“…Although a high response to gas molecules was achieved in that report, the mass producing and integrating of graphene into a real device remained a challenge to be overcome. With that goal in mind, many researchers have developed high-performance NO 2 gas sensors using reduced graphene oxide sheets, obtained from high temperature annealing [9] or a chemical conversion with hydrazine [10] and ascorbic acid [11], for application as a low-cost, simple and practical sensor device. More recently, Joshi et al [12] reported a NO 2 gas sensor based on graphene films and ribbons grown on Ni-coated Si substrates using the microwave plasma enhanced chemical vapor deposition (MPECVD) method.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs provide high surface area, then help the dispersion of the sensing materials on the nanotube walls (Figure 5a). The better performance of these hybrid sensors are also attributed to the effective electron transfer between the metal oxide particles and the highly conductive carbon nanotube network [42][43][44]. CNTs could also be coated with metal oxides of controlled thickness [45].…”
Section: Sensing Materialsmentioning
confidence: 99%
“…Sun et al fabricated flexible H 2 sensors on plastic substrates using necklace-like structures of Pd NPs electrochemically deposited on SWCNT networks (Sun & Wang 2007). MWCNTs decorated with discrete SnO 2 NPs showed room-temperature gas sensing capability for low concentration gases (H 2 , CO, and NO 2 ) diluted in air (Lu et al 2009). In fuel cells, the catalytic activity of metal NPs for the electro-oxidation of fuel molecules strongly depends on the size and the shape of NPs (Valden et al 1998), the type of catalyst support (Wolf & Schuth 2002), and the method of catalyst preparation .…”
Section: Cnt-np: a New Class Of Multifunctional Nanomaterialsmentioning
confidence: 99%
“…CNTs decorated with NPs form a new class of hybrid nanomaterials that could potentially display not only the unique properties of NPs (Fissan et al 2003;Scher et al 2003) and nanotubes (Dresselhaus et al 2001;de Heer 2004;), but also additional novel physical and chemical properties due to the interaction between CNTs and attached NPs. These hybrid nanomaterials have recently been shown as promising building blocks for various applications, including gas sensors (Kong et al 2001;Sun & Wang 2007;Lu et al 2009), fuel cells (Mu et al 2005;Kongkanand et al 2006;Robel et al 2006), solar cells (Landi et al 2005;Guldi et al 2006;Kongkanand et al 2007; Lee et al 2007), Li-ion batteries (Zhang et al 2006), hydrogen storage Anson et al 2006), and transparent conductive electrodes (Kong et al 2007). This chapter begins by outlining the significance of CNT-NP hybrid structures in terms of materials advantages and potential applications.…”
Section: Introductionmentioning
confidence: 99%